Comparison on the effect of homogeneous and inhomogeneous body on antenna performance and SAR - Othman, N. (2012)
This research quantifies the effect of homogeneous and inhomogeneous body model on Specific Absorption Rate (SAR). Quarter wave monopole antenna is used as the excitation source at 2.4 GHz. The simulation results are calculated by means of CST Microwave Studio based on Finite Integration Technique (FIT). Male Voxel model is modelled as an inhomogeneous and homogeneous models and filled with standard dielectric properties (σ,εr) of 2.4 GHz as recommended by the FCC. The antenna is placed in front of the body model in the area of human wrist and the distances are varied (5, 10, 20, 31, 50, and 62 mm). The results are presented in terms of resonant frequency, radiation pattern, and SAR. The effect of homogeneity is negligible on the return loss and radiation pattern. However the 10g SAR is increased by 20% when the homogeneous model is used.